The Pianist's Guide to Pedaling - Banowetz, Joseph (Bloomington Indiana University Press, 1992)
Joseph Banowetz and four distinguished contributors provide practical suggestions and musicological insights on the pedaling of keyboard works from the 18th to the 20th century.
Keywords: 18th Century (1701-1800); 19th Century (1801-1900); 20th Century (1901-2000); Piano; Pedal